Antidepressant activity: contribution of brain microdialysis in knock-out mice to the understanding of BDNF/5-HT transporter/5-HT autoreceptor interactions - Gardier, Alain M. (Frontiers in Pharmacology, 2013)
Why antidepressants vary in terms of efficacy is currently unclear. Despite the leadership of selective serotonin reuptake inhibitors (SSRIs) in the treatment of depression, the precise neurobiological mechanisms involved in their therapeutic action are poorly understood. A better knowledge of molecular interactions between monoaminergic system, pre- and post-synaptic partners, brain neuronal circuits and regions involved may help to overcome limitations of current treatments and identify new therapeutic targets. Intracerebral in vivo microdialysis (ICM) already provided important information about the brain mechanism of action of antidepressants first in anesthetized rats in the early 1990s, and since then in conscious wild-type or knock-out mice. The principle of ICM is based on the balance between release of neurotransmitters (e.g., monoamines) and reuptake by selective transporters [e.g., serotonin transporter for serotonin 5-hydroxytryptamine (5-HT)]. Complementary to electrophysiology, this technique reflects pre-synaptic monoamines release and intrasynaptic events corresponding to ≈80% of whole brain tissue content. The inhibitory role of serotonergic autoreceptors infers that they limit somatodendritic and nerve terminal 5-HT release. It has been proposed that activation of 5-HT1A and 5-HT1B receptor sub-types limits the antidepressant-like activity of SSRIs. This hypothesis is based partially on results obtained in ICM experiments performed in naïve, non-stressed rodents. The present review will first remind the principle and methodology of ICM performed in mice. The crucial need of developing animal models that display anxiety and depression-like behaviors, neurochemical and brain morphological phenotypes reminiscent of these mood disorders in humans, will be underlined. Recently developed genetic mouse models have been generated to independently manipulate 5-HT1A auto and heteroreceptors and ICM helped to clarify the role of the pre-synaptic component, i.e., by measuring extracellular levels of neurotransmitters in serotonergic nerve terminal regions and raphe nuclei. Finally, we will summarize main advantages of using ICM in mice through recent examples obtained in knock-outs (drug infusion through the ICM probe allows the search of a correlation between changes in extracellular neurotransmitter levels and antidepressant-like activity) or alternatives (infusion of a small-interfering RNA suppressing receptor functions in the mouse brain). We will also focus this review on post-synaptic components such as brain-derived neurotrophic factor in adult hippocampus that plays a crucial role in the neurogenic and anxiolytic/antidepressant-like activity of chronic SSRI treatment. Limitations of ICM will also be considered.